Designing winning products - Woodside, Arch G.; Liukko, Timo; Lehtonen, Ari (Advances in business marketing and purchasing ;, 2000)
Written for marketing executives, new product/service managers, and marketing research professionals, "Designing Winning Products" (DWP) focuses on design and market testing issues/solutions for new business-to-business products and services. The first three chapters synthesize the product innovation literature; the objective of these chapters is to increase marketing and product managers' technical skills for testing customer acceptance of alternative new product/service designs. Detailed examples of applying these skills are described in seven later chapters - these chapters describe how to apply conjoint analysis and choice experiments with B-to-B customers in specific European and North American markets. A chapter is devoted to describing how superior new products sometimes fail to attract known customers - the nitty-gritty nuances behind the innovator's dilemma. More than 50 diagrams, tables and figures support the text; the chapter discussions and end-of-chapter references include more than 300 complete citations to additional sources.